Edukasi dan Pendidikan Kesehatan Menstruasi pada Remaja Putri Di SMP Negeri Kabupaten Mamuju - Parwati, Dewi; Thalib, Kiki Uniatri; Susanti, Susanti; Darmansyah, Safriadi; Sallo, Andi Kamal M; Manuntungi, Andi Ernawati; Susiandari, Ariawati; D, Yuliana; Rabuana, Susi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Pubetas is a time when a child experiences physical, psychological changes and maturation of sexual function. Puberty in our lives usually starts when we are eight to ten years old and ends around the age of 15 to 16 years. The aim of this research was to determine the menstrual cycle of female students at SMP Negeri Kab. Mamuju, which is a city that is developing with the influence of a metropolitan lifestyle. The type of research carried out was analytical, with a cross sectional approach. Sampling was carried out using a stratified proportional random sampling technique. The researcher took subjects proportionally at each level to obtain a sample of 209 female students at the District Public Middle School. Mamuju. The data used in this research is primary data. Data analysis used univariate and bivariate analysis with the chi-square test. The results of the research show that most of the female students at SMP Negeri Kab. Mamuju experiences an abnormal menstrual cycle of 50.72%, female students whose age is included in the mid-teens category 14-16 years old is 43.54%, female students with physical activity who are included in the heavy physical activity category are 82%, female students with physical activity status nutrition included in the overweight category was 36.36%, and female students included in the stress category was 37.32%. Variables that have a significant relationship with the menstrual cycle are age, physical activity, nutritional status, and stress. With the age value of female students X² count is 6.089 > X²table is 3.84 with db = 1. Physical activity db = 2. Stress X² count is 62.346 >.